A structural peculiarity of Antarctic fish IgM drives the generation of an engineered mAb by CRISPR/Cas9 - Ametrano, Alessia; Miranda, Bruno; Moretta, Rosalba; Dardano, Principia; De Stefano, Luca; Oreste, Umberto; Coscia, Maria Rosaria (Frontiers in Bioengineering and Biotechnology, 2024)
IgM is the major circulating Ig isotype in teleost fish, showing in Antarctic fish unique features such as an extraordinary long hinge region, which plays a crucial role in antibody structure and function. In this work, we describe the replacement of the hinge region of a murine monoclonal antibody (mAb) with the peculiar hinge from Antarctic fish IgM. We use the CRISPR/Cas9 system as a powerful tool for generating the engineered mAb. Then, we assessed its functionality by using an innovative plasmonic substrate based on bimetallic nanoislands (AgAuNIs). The affinity constant of the modified mAb was 2.5-fold higher than the one obtained from wild-type mAb against the specific antigen. Here, we show the suitability of the CRISPR/Cas9 method for modifying a precise region in immunoglobulin gene loci. The overall results could open a frontier in further structural modifications of mAbs for biomedical and diagnostic purposes.